DISORINTASI SELF REGULATED LEARNING DAN MOTIVASI DALAM MEMUPUK NALURI BERPRESTASI MAHASISWA - Dewa Ayu Made Manu Okta Priantini dan I Putu Suardipa (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
Self regulated learning is a condition where individuals develop an understanding of which responses are appropriate and which are not appropriate, as well as controlling and monitoring individual behaviors themselves. Self regulated learning is the self-regulation of learning in students who have three phases namely goals, strategic planning, and understanding. Effective learning strategies as well as motivation and persistence apply this strategy until the task is completed by satisfying them, it is likely that they are effective learners. Self regulated learning is a good target for student intervention because students can learn to become independent learners. self regulated learning is the self-regulation of learning refers to the process by which students systematically focus their thoughts, feelings, and actions, on achieving goals, so as to survive long-term tasks until the task is completed. Disorintasi self regulated learning triggers self-regulation in learning that is carried out independently in displaying a series of actions aimed at achieving the target or learning objectives by processing strategies in performing cognition, behavior, and motivation that can indirectly improve student achievement.